What's Spanish for development? Chilean higher education at an impasse - Leihy, P; M Salazar, J (Centre for Global Higher Education, University of Oxford, 2021)
This paper contemplates the expansion of Chilean university education, particularly in terms of the country’s current lack of confidence and certainty. It introduces and applies calliopemetric analysis, measuring the passage of a sense of epic through time. A range of graphs and accompanying commentary track, from various angles, changing notions of higher education’s promise on the part of Chileans and system oversight, and the funding of the enterprise.